Optimizing Sales of MSME Products in Pandean Tourism Village through Marketplace Account Creation and Management Training - Setiati, Fita; Setiawan, Mohamad Arief; Aalin, Elmi Rakhma; Alawia, Mutia Tsalitsa; Athoillah, Ahmad Saifi; Asmoro, Wiwiek Kusumaning (Jurnal Abdimas, 2025)
The community service program conducted in Pandean Tourism Village focuses on increasing the capacity of MSMEs to utilize marketplace platforms to optimize their product sales. This program is motivated by the significant potential of local MSME products, but they still face challenges in digital marketing, particularly in utilizing marketplaces, which are currently an effective sales channel. Through this training, MSMEs are taught everything from creating a marketplace account, product photography techniques, writing compelling descriptions, and online store management strategies. The results of this community service program demonstrate an increase in participants' understanding and skills in managing Pandean Tourism Village's online store in the marketplace. MSMEs are expected to be able to independently create marketplace accounts, upload products with attractive photos and descriptions, and manage orders more professionally. The success of this program is measured not only by the participants' increased knowledge but also by the number of orders received through the marketplace platforms they manage, indicating that the program has had a direct impact on increasing sales of MSME products in Pandean Tourism Village.